Implementasi Terapi Munajat dalam Konseling Islam untuk Membentuk Kebiasaan Positif Siswa: Studi Kasus di SMP Negeri 1 Siman Ponorogo - Muhammad Sabilillah; Nabilla; M. Nasih Mu'awan; Rifqi Surya Pratama Gunawan (Jurnal Muria Research Guidance and Counseling (MRGC), 2026)
This study aims to analyze the effectiveness of munajat therapy as an Islamic counseling technique in fostering positive habits among students in the tahfidz Al-Qur'an program at SMPN 1 Siman Ponorogo. A qualitative case study design was employed, with participants selected through purposive sampling, comprising students actively involved in munajat therapy sessions and Islamic guidance and counseling (BK) teachers. Data were collected through participatory observation, semi-structured interviews, and documentation. Data validity was ensured through source triangulation, technique triangulation, and member checking. Thematic analysis was applied through data reduction, data presentation, and conclusion drawing. The findings demonstrate that munajat therapy effectively shifted students' religious behavioral patterns from the "rarely" and "never" categories to "frequent" across almost all observed indicators, reflecting a transformation of motivation from extrinsic to intrinsic. Improvements were also observed in self-discipline, self-regulation, spiritual awareness, and psychological well-being. The effectiveness of this therapy is influenced by the consistency of its application, the active role of BK teachers, and a school environment that upholds religious values. This study contributes a specific empirical examination of munajat therapy as a structured counseling technique in a general junior high school setting, filling a gap in prior literature that has been predominantly theoretical or focused on adult populations. Future research is recommended to expand the scope to other educational levels using mixed methods approaches.